2022
DOI: 10.3847/psj/aca402
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering Behavior of Rough, Polycrystalline Mercury Analogs

Abstract: The solar wind continuously impacts on rocky bodies in space, eroding their surface, thereby contributing significantly to the exosphere formations. The BepiColombo mission to Mercury will investigate the Hermean exosphere, which makes an understanding of the precise formation processes crucial for evaluation of the acquired data. We therefore developed an experimental setup with two microbalances that allows us to compare the sputter behavior of deposited thin solid layers with that of real mineral samples in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 37 publications
(65 reference statements)
1
18
0
Order By: Relevance
“…This is not due to impacts realistically occurring at normal incidence in nature, but due to surface roughness leading to locally reduced incidence angles for shallow impinging ions and therefore flattened mass yield distributions. This is discussed in Biber et al (2022) for enstatite irradiation experiments and was previously shown for rough Bo and Be surfaces (Gauthier et al 1990;Roth et al 1991;Küstner et al 1999).…”
Section: Sputter Yieldsupporting
confidence: 55%
See 3 more Smart Citations
“…This is not due to impacts realistically occurring at normal incidence in nature, but due to surface roughness leading to locally reduced incidence angles for shallow impinging ions and therefore flattened mass yield distributions. This is discussed in Biber et al (2022) for enstatite irradiation experiments and was previously shown for rough Bo and Be surfaces (Gauthier et al 1990;Roth et al 1991;Küstner et al 1999).…”
Section: Sputter Yieldsupporting
confidence: 55%
“…5. Biber et al (2022) used the in-house-built ray-tracing code SPRAY (Cupak et al 2021) with data from SDTrimSP and atomic force microscope images to discuss the effect of surface roughness on the sputter yield of a powder pellet and a flat, glassy thin film. They found that a rough pressed pellet surface reduces the yield, especially at shallow incident angles (above 45°r elative to surface normal).…”
Section: Sputter Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that ion sputtering yields are highly dependent on the incidence angle (Behrisch & Eckstein 2007;Szabo et al 2020b), and the SW impact angle is often approximated as either normal (Nénon & Poppe 2020;Killen et al 2022) or 45°angle relative to a flat surface (Jäggi et al 2021). In addition, because the surfaces of airless bodies are not flat but composed of individual grains with varied size distributions, the incoming SW ions impact the surface at many different relative angles, further affecting the yield (Wehner et al 1963;Szabo et al 2018Szabo et al , 2022aBiber et al 2020Biber et al , 2022. This has been modeled as a parallel flow of incident ions, which is equivalent to a cosine distribution of impact angles onto a flat surface (see, e.g., Cassidy & Johnson 2005).…”
Section: Approximations In Previous Binary Collision Approximation Mo...mentioning
confidence: 99%